If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (W + 5)(W + -6) = 0 Reorder the terms: (5 + W)(W + -6) = 0 Reorder the terms: (5 + W)(-6 + W) = 0 Multiply (5 + W) * (-6 + W) (5(-6 + W) + W(-6 + W)) = 0 ((-6 * 5 + W * 5) + W(-6 + W)) = 0 ((-30 + 5W) + W(-6 + W)) = 0 (-30 + 5W + (-6 * W + W * W)) = 0 (-30 + 5W + (-6W + W2)) = 0 Combine like terms: 5W + -6W = -1W (-30 + -1W + W2) = 0 Solving -30 + -1W + W2 = 0 Solving for variable 'W'. Factor a trinomial. (-5 + -1W)(6 + -1W) = 0Subproblem 1
Set the factor '(-5 + -1W)' equal to zero and attempt to solve: Simplifying -5 + -1W = 0 Solving -5 + -1W = 0 Move all terms containing W to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1W = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1W = 0 + 5 -1W = 0 + 5 Combine like terms: 0 + 5 = 5 -1W = 5 Divide each side by '-1'. W = -5 Simplifying W = -5Subproblem 2
Set the factor '(6 + -1W)' equal to zero and attempt to solve: Simplifying 6 + -1W = 0 Solving 6 + -1W = 0 Move all terms containing W to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1W = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1W = 0 + -6 -1W = 0 + -6 Combine like terms: 0 + -6 = -6 -1W = -6 Divide each side by '-1'. W = 6 Simplifying W = 6Solution
W = {-5, 6}
| 3(5m-7)-2(9m-11)=4(8m-13)-17 | | 1/3-2/7u=-1/2 | | (6.3x^-1/4)-.35=0 | | 6.3x^-1/4-.35=0 | | X-5=-1.5x+2.5 | | x^4+8x^2-4=0 | | 0.16x+1.50=2 | | -(6b)/(10b-8) | | 35+x=65 | | (-9x^3+7x^2-9x+8)+(10x^3+8x^2-6x-3)= | | x+x=74 | | x+y+4=50 | | 2(x+1)+(x-1)=7 | | 25x/100-x | | 25x/100-x^100 | | 5x-(2x+9)=4x-2 | | -6.2(2t+4)-1.6(4t-6)= | | 7(x-4)=x-4(x+1) | | 3x+x=88000 | | 3(6x-5)=5(9-4x) | | solveax^3+bx-c=0forx | | 4x+x=1350 | | 18x-15=45-20x | | z^2=p^2+q^2 | | X+0.6X=140 | | 2y-5=-12+9y | | x^4+4-4x^2-16=0 | | 7y-18=-2+9y | | 5(x+4)=7(x-7) | | 2m^2-7m-3=-10 | | 5*3=28 | | 2(-1)+6=8 |